The effect of catalyst on soil stabilization by application of lime - Wan Zalik, Wan Ewirda (2009)
Soft cohesive clays are normally associated with large settlements and low strength. Various techniques are available to reduce the problem. One of the low cost techniques is to modify the soil with lime in-situ to make it workable for construction and allow it to increase in strength by pozzolanic reactions between lime and clay minerals. The addition of lime to a soil has a pronounced effect on its physical and chemical properties. It is known to be an effective stabilization method for clayey soil. However, due to the variation of soil minerals and clay fraction, the degree of pozzolanic reactions varies. Addition of catalyst i.e. zeolite may improve the performance of lime stabilization. There are two types of zeolites which are natural zeolite and synthetic zeolite. A series of laboratory tests has been carried out to investigate the effect of zeolite on the performance of lime stabilization. Unconfined Compressive Test on 36 sets of samples has been carried out for 0,7,14, 28 and 56 days of curing. The addition of synthetic zeolite in lime-kaolin stabilized soil has increased the soil strength by 255% at 56 days curing period at the design mix of kaolin + 6% lime +15% zeolite. The higher value of UCS indicates that zeolite is an effective catalyst to enhance lime stabilization.